Ferry Tale Felicity - Mohd Azad Rosdi, Nor Azidi; Ramly @ Amat, Annurimah; Alimudin, Noor Anunsuhada; Ag Yussof, Dgku Siti Nurafiqah Ramizah (2013)
Our company's name is Ferry Tale felicity and we are providing transportation and restaurant facility in the ship service to everyone, which are mostly tourism and local society that are interest to travel with our ship. Our business location is at, Kota Kinabalu Office R31, Jesselton Point Ferry Terminal, Kota Kinabalu Sabah.We perform a partnership business for this service. Each of us had our own tasks and responsibilities in every position, whereby General Manager is Nor Azidi bin Mohd Azad. Administration Manager is also Nor Azidi bin Mohd Azad, Marketing Manager is Noor Anunsuhada binti Alimudin. Operation Manager is Annurimah bt Ramly@Amat, and Financial Manager is Dgku Siti Nurafiqah Ramizah bte Ag yussof. Each of this position is very important to ensure the business objective, vision and mission can be achieved. In this partnership business, we already make an agreement which is agreed by every member.